All-Inorganic CsPbBr3 Perovskite Nanocrystals Synthesized with Olive Oil and Oleylamine at Room Temperature - Getachew Welyab; Mulualem Abebe; Dhakshnamoorthy Mani; Aparna Thankappan; Sabu Thomas; Fekadu Gochole Aga; Jung Yong Kim (Micromachines, 2023)
Room temperature (RT) synthesis of the ternary cesium lead bromide CsPbBr3 quantum dots with oleic acid and oleylamine ligands was developed by Zeng and coworkers in 2016. In their works, the supersaturated recrystallization (SR) was adopted as a processing method without requiring inert gas and high-temperature injection. However, the oleic acid ligand for haloplumbate is known to be relatively unstable. Hence, in this work, we employed the eco-friendly olive oil to replace the oleic acid portion for the SR process at RT. Resultantly, we found that the cube-shaped nanocrystal has a size of ~40–42 nm and an optical bandgap of ~2.3 eV independent of the surface ligands, but the photoluminescence lifetime (τav) and crystal packing are dependent on the ligand species, e.g., τav = 3.228 ns (olive oil and oleylamine; here less ordered) vs. 1.167 ns (oleic acid and oleylamine). Importantly, we explain the SR mechanism from the viewpoint of the classical LaMer model combined with the solvent engineering technique in details.